Impact of the Luding Earthquake on the Area of Potentially Suitable Habitat for Batrachuperus Species in the Gongga Mountain National Nature Reserve - Xinlong Song; Xiuying Liu; Xiaoao Zheng; Jian Song; Zhangqiang You; Jianli Xiong (Animals)
Members of the genus Batrachuperus are endemic to China and include seven described species, five of which are nationally protected salamanders in China. The Gongga Mountain National Nature Reserve (GGMNNR) is rich in animal and plant resources, including the Batrachuperus species. On 5 September 2022, the GGMNNR experienced the Luding earthquake, and this provided an opportunity to quantify the impact of a catastrophic events on the area of potentially suitable habitat for a rare species in the GGMNNR. The main objective of this study was to evaluate the impact of the Luding earthquake on the area of potentially suitable habitat for the Batrachuperus species by combining Maxent modeling, remote sensing image processing, and GIS methods. The results showed that precipitation, temperature, and slope were the most important variables affecting the distribution of the Batrachuperus species. Currently, suitable habitats accounted for 40.67% (1664.10 km2) of the studied area (4091.10 km2), and these areas were mainly distributed in the northern, western, and southern portions of the GGMNNR. The destruction caused by the earthquake accounted for 4.87% (199.34 km2) of the studied area, and only 1.97% (32.78 km2) of the suitable habitat of the Batrachuperus species was destroyed. These results indicated that although the Luding earthquake affected the habitat of the Batrachuperus species in the GGMNNR, its effect was small. These findings enhance our understanding of the distribution of the Batrachuperus species and the effect of the Luding earthquake on biodiversity in the GGMNNR.